Ethical Mindsets: Learning from Cultural Comparisons - Issa, Theodora (2016)
This chapter provides a very brief idea of the concept ‘Ethical Mindsets’ in an international context, which enhances the idea of the existence of different cultures, an understanding that will assist in enhancing the capacity building. ‘Ethical mindsets’ have been recently investigated deriving from two literatures ‘spirituality and aesthetics’ and was defined as ‘…an appreciation of and reflection on any situation through the filter of personal beliefs and values such as honesty, integrity, harmony, balance, truth seeking, making a difference, and demonstrating professionalism, deriving from the strength rooted in individual’s inner-self’ (Issa 2009, p. 163).